Compensation of Technological Error During Thread Cutting - Urinov Nasullo Fayzullaevich; Zainiev Khudoyberdi Mukhiddinovich (Zien Journals, 2022)
The article covers one of the factors affecting the processing kinematic threads procedure and contributing to decrease in the error in the manufacture of threads - the size of the removed allowance. Generally, we will focus on allowance for the final processing, where all accuracy parameters must be complied.
Keywords: kinematic thread; thread pitch error; screw-grinding machine; technological error